Current Developments in Monetary and Financial Law, Volume 2. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The papers published in this volume are based on an IMF seminar held in 2000 that covered a broad range of topics on monetary and financial law, such as the liberalization of capital movements, data dissemination, responsibilities of central banks, and the IMF's goals in financial surveillance and architecture. Participants addressed recent issues in the financial sector, including those related to payment systems and supervision of financial institutions. Updates dealt with Internet banking, bank secrecy, and currency arrangements-including dollarization. Participants discussed the recent activities of the other international financial institutions, which included the European Central Bank and the International Finance Corporation. Prevention of financial crises was also discussed, with reference to the distinct roles of the IMF and the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet